Corporate Social Responsibility in the International Banking Industry - Scholtens, Bert (Journal of business ethics, 2009)
This article aims at providing a framework to assess corporate social responsibility with international banks. Currently, it is mainly rating institutions like EIRIS and KLD that provide information about firms’ social conduct and performance. However, this is costly information and it is not clear how the rating institutions arrive at their conclusion. We develop a framework to assess the social responsibility of internationally operating banks. We apply this framework to more than 30 institutions and find significant differences among individual banks, countries, and regions. Furthermore, it appears that social responsibility of these banks has significantly improved between 2000 and 2005.